2018
DOI: 10.1093/mnras/sty2006
|View full text |Cite
|
Sign up to set email alerts
|

A jet model for the fast IR variability of the black hole X-ray binary GX 339-4

Abstract: Using the simultaneous Infra-Red (IR) and X-ray light curves obtained by Kalamkar et al. (2016), we perform a Fourier analysis of the IR/X-ray timing correlations of the black hole X-ray binary (BHB) GX 339-4. The resulting IR vs X-ray Fourier coherence and lag spectra are similar to those obtained in previous studies of GX 339-4 using optical light curves. In particular, above 1 Hz, the lag spectrum features an approximately constant IR lag of about 100 ms. We model simultaneously the radio to IR Spectral Ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 62 publications
(79 reference statements)
5
72
1
Order By: Relevance
“…Its optical/X-ray CCF has a similar peak, but complemented by the precognition dip (Gandhi et al 2010). The single-peak CCF has been successfully modelled using the jet internal shocks scenario (e.g., Malzac et al 2018), and the short delay in this model corresponds to the propagation time between the central engine and the region of maximal IR radiation within the jet. The observed CCF in MAXI J1820+070 peaks at time lags which are at least an order of magnitude higher than those detected in GX 339-4, and is more consistent with those of Swift J1753.5-0127, thus supporting the irradiated disc scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Its optical/X-ray CCF has a similar peak, but complemented by the precognition dip (Gandhi et al 2010). The single-peak CCF has been successfully modelled using the jet internal shocks scenario (e.g., Malzac et al 2018), and the short delay in this model corresponds to the propagation time between the central engine and the region of maximal IR radiation within the jet. The observed CCF in MAXI J1820+070 peaks at time lags which are at least an order of magnitude higher than those detected in GX 339-4, and is more consistent with those of Swift J1753.5-0127, thus supporting the irradiated disc scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Lags: The IR 0.1 second lag observed at high frequencies is easily explained in terms of travel time of the fluctuations from the inflow to the jet (Malzac 2014;Malzac et al 2018). Malzac et al (2018) have shown that also the negative lags observed at low frequencies can be accounted for by the model, due to a differential response of the shocks together with Doppler boosting modulation. Also in this case, dedicated simulations are in order to quantify this scenario for this dataset.…”
Section: Compact Jet -Internal Shocksmentioning
confidence: 98%
“…In this scenario, the whole IR variable emission is interpreted in terms of synchrotron emission from a jet, in which shells with different velocity collide and dissipate their differential energy (Jamil et al 2010;Malzac 2014;Malzac et al 2018). The shell Lorentz factor PSD is assumed to be identical to the X-ray PSD, which is assumed to be a proxy for the accretion rate.…”
Section: Compact Jet -Internal Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesizing these results, a possible scenario is then that the disc is recessed between large flares, with a quasi-steady compact jet. Transient instabilities in the jet could give rise to rapid optical flaring (Malzac et al 2018). During major flares, the disc moves inward with the flare then ending with disruption of this transient disc and ejection of a plasmon, leading to a delayed optical flare (Mirabel et al 1998).…”
Section: Rapid Variability and The Central Engine Geometrymentioning
confidence: 99%